Volatile Organic Compounds (VOCs) and Interleukin-23 Levels in Lung Cancer: A Future Biomarker - Raden Dicky Wirawan Listiandoko; Ungky Agus Setyawan; Tri Wahju Astuti; Susanthy Djajalaksana; Aditya Sri Listyoko; Arinto Yudi Ponco (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Lung cancer (LC) is the world's second leading cause of death due to malignancy. In Indonesia, LC is one of the top three malignancies. Volatile organic compounds (VOCs) from the respiratory reflect changes in metabolism caused by disease and may be a biomarker of LC. Interleukin-23 (IL-23) has been known as a pro-inflammatory cytokine in the development and progression of cancer. This study aimed to identify levels of IL-23 and VOCs in LC patients. Methods: This study involved 40 LC patients and 42 controls. VOCs were taken by the subject exhaling their third deep breath into the sample bag, which was immediately analyzed using an E-nose-based device. As for the IL-23, the cytokine was taken from the blood serum and then analyzed using the ELISA method. Kolmogorov-Smirnov and Shapiro-Wilk tests were performed to test data normality. Mann-Whitney and Kruskal Wallis tests were conducted for variables. Spearman correlation and heat map were used to find the correlation between the observed gases and IL-23. Results: The concentration of ozone (p = 0.000), ethanol (p = 0.000), formaldehyde (p = 0.000), toluene (p = 0.000), acetone (p = 0.000), ammonia (p = 0.000), ammonium (p = 0.001), nitrogen (p = 0.001) and methane (p = 0.000) in LC group differed with controls. The same outcome was also observed in comparing LC patients and control groups of IL-23 (p = 0.000). Spearman correlation analysis revealed a positive correlation between serum IL-23 with formaldehyde (p = 0.029), toluene (p = 0.014), and ammonia (p = 0.028) and a negative correlation with nitrogen (p = 0.011). Compared to the control group, all types of LC were observed to have higher levels of IL-23. A weak positive correlation was found in formaldehyde (Cv = 0.23), toluene (Cv = 0.23), and ammonia (Cv = 0.13). A weak negative correlation was obtained in acetone (Cv = -0.12), ammonium (Cv = -0.11), and nitrogen dioxide (Cv = 0.23). Conclusion: Weak linear correlations were obtained between the cytokine and formaldehyde, toluene, ammonia, ammonium, and nitrogen dioxide. A higher IL-23 concentration was observed in the LC group than in the control group. The volatile concentration was significantly different between LC and control groups.